Mapping Russian International Relations: A Topic Modelling Approach - I. Khludov; V. Vinogradov; N. Neklyudov (Международная аналитика)
This study examines the landscape of Russian International Relations (IR) scholarship, oﬀering a quantitative analysis of thematic trends in Russian IR publications using data from the OpenAlex bibliographic database. We employed Structural Topic Modeling (STM) on 13,705 articles published between January 2000 and May 2024, ensuring methodological rigor through language standardization, text preprocessing, and exclusion of irrelevant texts. While prior research on Russian IR has mostly been descriptive, often focusing on typologies or prescriptive arguments, our study uncovers several underexplored attributes. Notably, Soviet-era legacies persist thematically rather than paradigmatically, and developmental issues such as inequality and justice are disproportionately represented. The systemic approach remains dominant, with Russian scholarship striving to integrate regional perspectives into the global context. Traditional focuses on Russian foreign policy and its great-power status persist, with a shift from identity issues to reinforcing this status. Despite strained relations with Europe, it remains a key focus in Russian works. Interestingly, topics on education and culture now surpass those on conflict and security, although this may be influenced by data characteristics or OpenAlex indexing.